Temperature-driven shifts in hatchling sex ratios of olive ridley sea turtles: A cross-site review - Ragil Angga Prastiya; Suherni Susilowati; Imam Mustofa; Aditya Yudhana; Ryan Adi Taufiqurrahman; Muhammad Athalah Daffa; Samira Musa Sasi; Nagia Musa Alghoul; Wiyanto Haditanojo (Continental Shelf Research, 2026)

Paternal lead exposure induces transgenerational oxidative stress and down-regulation of antioxidant genes in Drosophila melanogaster - Aminu Argungu Umar; Isah Musa Fakai; Mustapha Umar Imam; Abduljalil Muhammad Mode (Environmental Science and Pollution Research, 2026)

Cross compartment microplastic contamination in the Gembong River estuary: Evidence from brackish water, sediment, and mullet (Mugil cephalus) - Nanik Retno Buwono; Muhammad Musa; Pratama Diffi Samuel; Rakhel Marsyanda Vanny; Nuril Aprilia Putri; Aprilian Trida Larasati (Regional Studies in Marine Science, 2026)

Evaluating the effect of Iron biofortification on nutraceutical and aromatic profiles of cereal grains: A case study of pearl millet - Hamza M.A. Abaker; Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Muhammad Arslan; Gustav Komla Mahunu; Zhuhai Li; Xiaodong Zhai; Abdalbasit Adam Mariod; Mohammad Rezaul Islam Shishir; Magdi Ali Osman Mohammed; Ahmed Gaafar Mohammed Elgorashi; Alaa K.M. Khogly; et al. (Food Chemistry, 2026)

Transgenerational effects of maternal lead exposure on oxidative stress and antioxidant defense mechanisms in Drosophila melanogaster - Abduljalil Muhammad Mode; Isah Musa Fakai; Mustapha Umar Imam; Aminu Argungu Umar (Toxicology and Environmental Health Sciences, 2026)

Widespread Use of Banned Pesticides and Weak Regulatory Enforcement: Environmental and Health Implications Among Farmers in Gombe State, Nigeria - Mohammad Bashir Sulaiman; Babangida Hammani; Abdullahi Muhammad Gimba; Oluyinka Omoyeni Akinlotan; Aliyu Tijjani Fadawa; Umar Musa Kwami; Taibatu Idris Umar; Amina Muhammad Bello (Journal of Agromedicine, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

Synergistic Effects of Biochar with Phosphorus Fertilization on soil Biochemical Properties and Wheat Productivity - Nighet Musa; Khalid Saifullah Khan; Muhammad Azeem; Mah-Noor Azad; Mehnoor Khan; Nabeeha Javed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2026)

Beyond coherence: a DAC criteria review of Sri Lanka’s climate policy architecture - Chamara Senadeera; Abu Sadat Muhammad Sayem; Walter Leal Filho; Grace Farhat; Haruna Musa Moda; Ruvini Dissanayake (Regional Environmental Change, 2026)
Climate change is intensifying Sri Lanka’s exposure to multiple hazards, including floods, droughts, landslides, cyclones, coastal risks and heat stress, with growing consequences for livelihoods, infrastructure, public health and national development. This analysis evaluates whether Sri Lanka’s contemporary climate policy architecture is sufficiently coherent and operationally robust to support effective climate resilience. A qualitative policy analysis was undertaken of eight core national climate-related instruments, generated by analytically combining thirteen policy and institutional documents published between 2021 and 2025. The study employed NVivo-based content analysis and a structured benchmarking framework based on an adapted Organisation for Economic Co-operation and Development Development Assistance Committee framework, which assessed relevance, coherence, effectiveness, efficiency, equity and sustainability. The pilot coding process achieved an intercoder reliability score of 0.81, indicating strong agreement between coders. The findings indicate that Sri Lanka’s policy architecture performs strongly on relevance and coherence, with mean scores of 4.1 and 3.9, respectively, reflecting substantial strategic alignment with the country’s multi-hazard climate risk profile. However, effectiveness and efficiency remained moderate, with both recording mean scores of 3.1, while equity and gender considerations emerged as the weakest dimension at 3.0. Sustainability varied across instruments depending on the extent to which they incorporated operational monitoring, statutory review cycles and multi-year financing arrangements. Instruments with clearer SMART targets, operational monitoring, reporting and verification systems, designated institutional responsibilities and costed financing pathways performed more strongly than those relying on broad commitments or annualised budget structures. Overall, Sri Lanka’s principal climate governance challenge lies not in the absence of policy ambition, but in the incomplete institutionalisation of delivery systems needed to convert strategic coherence into measurable resilience outcomes. Aim of the study To critically evaluate the coherence and implementation robustness of Sri Lanka’s contemporary national climate policy architecture in order to determine whether strategic policy commitments are supported by adequate institutional design, financing arrangements, monitoring systems, equity safeguards and long-term sustainability in the context of escalating multi-hazard climate risks.

Safety and tolerability of the ACE-inhibitor lisinopril among Nigerian adults with HIV: preliminary pilot data from a randomized clinical trial - Faisal S. Dankishiya; Hamza Muhammad; Usman J. Wudil; Baba M. Musa; Liping Du; Ibrahim A. Adam; Aima A. Ahonkhai; Anna M. Burgner; Aishatu M. Nalado; Mahmoud U. Sani; Aliyu Abdu; Bryan E. Shepherd; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Fabrication and In-Vitro Evaluation of Floating Tablets of Levofloxacin Hemihydrate for the Local Treatment of Helicobacter Pylori Infection - Abdullah Khan; Asif Nawaz; Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Haroon Khan; Muhammad Musa Khan; Irum Farooq; Saima Mahmood (Journal of Pharmaceutical Innovation, 2026)

Assessment of Protective Role of Different Probiotic Strains against Bacterial and Endotoxin-Induced Sepsis in a Mouse Model - Sabeeka Sajjal; Hasnat Ahmad Bilal; Ambreen Zahra; Ayesha Saeed; Aiman Khan; Muhammad Musa Mubashar; Aisha Khatoon; Muhammad Imran Arshad (Probiotics and Antimicrobial Proteins, 2026)

Numerical simulation of breakdown threshold voltage in charging coils of wireless power transfer systems - Umar Musa; Abdullahi Abubakar Mas’ud; Johnatan M. Rodríguez-Serna; Abdullahi Mohammad; Muhammad Lotfi Hussain; Firdaus Muhammad-Sukki (Next Research, 2026)

Polydatin attenuates lead-induced hematotoxicity and neuroinflammation: insights from hematological, cytokine, and histopathological analyses in Wistar rats - Salisu Muhammad Highab; Abdulhakim Abubakar; Sanusi Muhammad Salisu; Rabiu Nuhu Danraka; Nawiyyu Musa; Mohammed Garba Magaji; Dalhatu Mukhtar Shehu; Jamilu Ya’u (Journal of Molecular Histology, 2026)

Involvement of the PD-1 pathway in the modulation of immune responses during allergic diseases - Asma’a Hassan Mohamed; Rithab Ibrahim Al-Samawi; Mohammad Chand Jamali; Sana Abdul-Jabbar Ali; Ayyub Ali Patel; Alam Eldin Musa Mustafa; Abdulrahman Samir Khairallah; Nasrin Mansuri; Ashit Kumar Dutta; Muhammad Zulfiqah Sadikan; Zaid H. Mahmoud (Inflammation Research, 2026)

Retraction Note: Do anthropogenic and natural factors elevate the haze pollution in the South Asian countries? Evidence from long-term cointegration and VECM causality estimation - Mohammad Musa; Lan Yi; Preethu Rahman; Muhammad Abu Sufyan Ali; Li Yang (Environmental Science and Pollution Research, 2026)

Experimental investigation of the mechanical and thermal behaviors of shear connectors in concrete sandwich panels - Madyan A. Al-Shugaa; Khalid Mohamed; Abubakr E. S. Musa; Amin Al-Fakih; Ridha A. A. Alhasan; Mohammed A. Al-Osta; Muhammad K. Rahman; Mohammed Rizwan Ali (Innovative Infrastructure Solutions, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

Development and validation of SR-DISVAXFIC: A mobile phone application for estimating the herd-level financial impact of small ruminant diseases and the potential benefits of vaccination in the field - Megan E. Rawlins; Adeyinka J. Adedeji; Victoria I. Ifende; Sandra I. Ijoma; Rebecca B. Atai; Joel Y. Atuman; Gambo Panzam; Haruna W. Gotom; Idris H. Adamu; Anas U. Musa; Isa M. Sani; Paul Adamu; et al. (Preventive Veterinary Medicine, 2026)

Neuroprotective Effects of Ficus deltoidea in Alzheimer’s Disease-Like Rat Model: Insights from Behavior, Histology, and Amyloid Pathology - Abdulhamid Sani Usman; Sushmitaa Dhevii Manoharan; Che Mohd Nasril Che Mohd Nassir; Hafizah Abdul Hamid; Zaw Myo Hein; Anwar Norazit; Jayakumar Murthy; Murizal Zainol; Mohd Amir Kamaruzzaman; Samaila Musa Chiroma; Muzaimi Mustapha; Mohamad Aris Mohd Moklas; et al. (Molecular Neurobiology, 2026)

Exploring the therapeutic potential of Nasturtium microphyllum (Boenn.) Rchb.: a combined in-vitro, in-vivo and in-silico approach - Rabia Khan; Muhammad Musa; Syed Mubassir Shah; Hussan Ara Begum; Alaa S. Alhegaili; Sajid Hussain; Atif Ali Khan Khalil; Sajid Ali (Inflammopharmacology, 2025)

Comparing microplastic contamination in vannamei shrimp aquaculture: the impact of concrete and HDPE pond materials in Probolinggo, East Java, Indonesia - Muhammad Musa; Muhammad Mahmudi; Evellin Dewi Lusiana; Sulastri Arsad; Aulya Martassha; Zalfa Nurul Abidah; Mafira Hanudya An Naba; Rakhel Marsyanda Vanny Alvionita; Nanik Retno Buwono (Aquaculture International, 2025)

Assessment of some trace elements in African catfish (Clarias gariepinus) from Hadejia-Nguru Wetlands, Northern Nigeria - Musa Alhaji Musa; Dahiru Sani; Abdulwakil Olawale Saba; Mohammad Noor Amal Azmai; Muhammad Farhan Nazarudin; Maimuna Ahmad Amshi (Environmental Monitoring and Assessment, 2025)

Impact of long-term cadmium exposure on insecticidal cross-resistance and biological traits of Brown planthopper Nilaparvata lugens (Hemiptera: Delphacidae) - Muhammad Musa Khan; Jin Wang; Yang Gao; Dongming Wu; Baoli Qiu; Zengrong Zhu (Journal of Hazardous Materials, 2025)

Disruption of midgut homeostasis by microplastics in Spodoptera frugiperda: Insights into inflammatory and oxidative mechanisms - Zeyun Fan; Muhammad Musa Khan; Kai Wang; Yihan Li; Fengliang Jin; Jing Peng; Xinyi Chen; Weizhen Kong; Xiaolu Lv; Xiaoyuan Chen; Baoli Qiu; Xingmin Wang (Journal of Hazardous Materials, 2025)

Linking provenance and diagenesis to reservoir quality evolution of sandstones: The Paleocene-Eocene Kerri-Kerri Formation, northeastern Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Usman Abubakar; Shehu Mukkafa; Ibrahim A. Kwami; Lukman U. Chiroma; Murtada Al-Hashem; Abubakar Yusuf; Abubakar S. Maigari; et al. (Marine and Petroleum Geology, 2025)

Effects of Encarsia formosa (Hymenoptera: Aphelinidae) parasitism on the feeding preference and performance of the whitefly predator Serangium japonicum (Coleoptera: Coccinellidae) - Yi-Han Li; Ze-Yun Fan; Zhan-Peng Zhu; Xiao-Lu Lv; Muhammad Musa Khan; Jing-Chen Sun; Bao-Li Qiu (Crop Protection, 2025)

Galactose-1-phosphate uridylyltransferase GalT promotes biofilm formation and enhances UV-B resistance of Bacillus thuringiensis - Aisha Lawan Idris; Xiao Fan; Wen Li; Hankun Pei; Musa Hassan Muhammad; Xiong Guan; Tianpei Huang (World Journal of Microbiology and Biotechnology, 2024)

Diagenesis and reservoir quality evolution of estuarine sandstones: Insights from the Cenomanian-Turonian Yolde Formation, northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Khalid Al-Ramadan; Murtada Al-Hashem; Aliyuda Kachalla; Usman Abubakar; Anas M. Salisu; Shehu Mukkafa; Ibrahim A. Kwami; Oluwafemi E. Aro; Muhammad Naveed Butt; et al. (Marine and Petroleum Geology, 2024)

Ecotoxicological insights into the effects of triflumezopyrim on P. fuscipes fitness, detoxification pathways, and gene expression - Muhammad Musa Khan; Yuanzheng You; Dylan O'Neill Rothenberg; Pankaj Bhatt; Shah Fahad; Ying Zhou; Zeng-Rong Zhu (Chemosphere, 2024)

In silico analysis of balsaminol as anti-viral agents targeting SARS-CoV-2 main protease, spike receptor binding domain and papain-like protease receptors - Daniel Danladi Gaiya; Aliyu Muhammad; Joy Sim Musa; Richard Auta; Anthony John Dadah; Rachael Oluwafunmilayo Bello; Madinat Hassan; Samuel Sunday Eke; Rebecca Imoo Odihi; Musa Sankey (In Silico Pharmacology, 2024)

Synthesis and characterization of bioplastics, Polyhydroxyalkanoates produced from sugarcane bagasse by using Bacillus cereus - Ting Kang Yong; Muhammad Nuwair Syahmi Musa; Rahmath Abdulla; Eryati Derman; Jualang Azlan Gansau; Mariani Rajin (Biocatalysis and Agricultural Biotechnology, 2024)

Sustainable development challenges in Bangladesh: an empirical study of economic growth, industrialization, energy consumption, foreign investment, and carbon emissions—using dynamic ARDL model and frequency domain causality approach - Mohammad Musa; Yanhua Gao; Preethu Rahman; Ahmad Albattat; Muhammad Abu Sufyan Ali; Swapan Kumar Saha (Clean Technologies and Environmental Policy, 2024)

High strength rubberized porous concrete for sustainable pavements: Engineering properties and life cycle assessment - Musa Ajmal Khan; Junaid Ahmad; Hammad Anis Khan; Muhammad Umer (Journal of Cleaner Production, 2024)

Modelling photoperiod in enhancing hydrogen production from Chlorella vulgaris sp. while bioremediating ammonium and organic pollutants in municipal wastewater - Fatima Musa Ardo; Kuan Shiong Khoo; Mohamad Zulfadhli Ahmad Sobri; Uganeeswary Suparmaniam; Baranitharan Ethiraj; Aliya Fathima Anwar; Sze Mun Lam; Jin Chung Sin; Muhammad Kashif Shahid; Sabah Ansar; Anita Ramli; Jun Wei Lim (Environmental Pollution, 2024)

Identification of potential inhibitors of shikimate kinase from Mycobacterium tuberculosis using in silico approach - Mustafa Alhaji Isa; Mohammed Mustapha Mohammed; Muhammad Musa Ibrahim; Falmata Audu Gubio; Fatimah Buba; Somia Shehzadi (Journal of Proteins and Proteomics, 2024)

Governance, fiscal expenditure, and economic growth in OIC countries: Role of natural resources and information communication technology - Naila Erum; Kazi Sohag; Jamaliah Said; Kazi Musa; Muhammad Mansoor Asghar (Resources Policy, 2024)

Distribution and accumulation of Cadmium in different trophic levels affecting Serangium japonicum, the predatory beetle of whitefly Bemisia tabaci, biologically, physiologically and genetically: An experimental study - Muhammad Musa Khan; Ze-Yun Fan; Xing-Min Wang; Bao-Li Qiu (Journal of Hazardous Materials, 2024)

Provenance history, depositional conditions andtectonic settings during late Cenomanian – early Turonian time in the Gongola Sub-Basin of the Upper Benue Trough Nigeria: Evidence from major and trace elements geochemistry of the Kanawa shales from the Pindiga Formation - Usman Abubakar; Simon V. Hohl; Musa Bappah Usman; Abubakar S. Maigari; Milan Stafford Tchouatcha; Raymond Peter Tabale; Abdulwahab Muhammad Bello; Auwalu Dalha; Shehu Mukkafa (Journal of African Earth Sciences, 2024)

Added value upshot of barley amalgamation in wheat flour to boost the physico-chemical quality attributes of flat bread - Muhammad Abdullah; Muhammad Zulkiffal; Tabussam Tufail; Farah Naz Akbar; Muhammad Owais; Javed Ahmed; Ahsan Javed; Muhammad Ijaz Tabassum; Amna Kanwal; Muhammad Asghar; Muhammad Musa; M. A. Rehman Arif; et al. (Cereal Research Communications, 2023)

A bioactive chalcone from the aerial parts of Indigofera conferta Gillet - Maryam Isah; Salima Murtala; Sakynah Musa Abdullahi; Asmau Nasiru Hamza; Nasir Tajuddeen; Mu’ammar Lawal Dauda; Vuyisa Mzozoyana; Aliyu Muhammad Musa (Natural Product Research, 2023)

Kinetic model derived from machine learning for accurate prediction of microalgal hydrogen production via conversion from low thermally pre-treated palm kernel expeller waste - Mohamad Zulfadhli Ahmad Sobri; Kuan Shiong Khoo; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sabah Ansar; Md Sohrab Hossain; Worapon Kiatkittipong; Chuxia Lin; Hui-Suan Ng; Juliana Zaini; Muhammad Roil Bilad; Man Kee Lam; et al. (Chemosphere, 2023)

Linking diagenesis and reservoir quality to depositional facies in marginal to shallow marine sequence: An example from the Campano-Maastrichtian Gombe Sandstone, Northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Muhammad A. Ismail; Shehu Mukkafa; Usman Abubakar; Ibrahim A. Kwami; Khalid Al-Ramadan; Abduljamiu O. Amao; Murtada Al-Hashem; Anas M. Salisu; Aliyuda Kachalla; Muhammad B. Abubakar; et al. (Marine and Petroleum Geology, 2023)

Comparative cyto-genotoxicity and clastogenicity properties of traditional trypanocidal Afrormosia laxiflora and Lonchocarpus laxiflorus plants in Wistar rats - Lovina Chinyere Ogbu; Aliyu Muhammad; Mohammed Aliyu Usman; Musa Bashir; Abdullahi Balarabe Sallau (Toxicology and Environmental Health Sciences, 2023)

Reviewing biohydrogen production from microalgal cells through fundamental mechanisms, enzymes and factors that engendering new challenges and prospects - Jia Min Woon; Kuan Shiong Khoo; Mehdi Akermi; Meznah M. Alanazi; Jun Wei Lim; Yi Jing Chan; Pei Sean Goh; Boredi Silas Chidi; Man Kee Lam; Juliana Zaini; Muhammad Roil Bilad; Yuguang Zhou; et al. (Fuel, 2023)

Study of geothermal and volcanic activity at Mount Awu, the deadliest active volcano in North Sulawesi Province, Indonesia using Optical Satellite Imagery - Bondan Galih Dewanto; Heryadi Rachmat; Estu Kriswati; Muhammad Yanis; Achmad Fakhrus Shomim; Admiral Musa Julius (Journal of Volcanology and Geothermal Research, 2023)

Bioactive Peptides from African Yam (AVIAIMF and GPADPF) and Taro (NGDF and NGNW) Reveal Multifunctional Antidiabetic Effects Using Biochemical and Cellular Models - Mohammed Auwal Ibrahim; June Cheptoo Serem; Aliyu Dantani Abdullahi; Suleiman Aminu; Abubakar Babando Aliyu; Aliyu Muhammad Musa; Bashir Musa; Megan J. Bester; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2023)

An insight into the mechanisms of action of selected bioactive compounds against epigenetic targets of prostate cancer: implications on histones modifications - Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Abdurrahman Pharmacy Yusuf; Yunus Aisha Lawal; Shehu Aisha Jibril; Hussaini Nuraddeen; Musa Mubarak Ibrahim; Idris Zubairu Sadiq; Murtala Bello Abubakar; Ibrahim Malami; Ibrahim Babangida Abubakar; Aliyu Muhammad (In Silico Pharmacology, 2023)

Microenvironment engineering of Fe-single-atomic-site with nitrogen coordination anchored on carbon nanotubes for boosting oxygen electrocatalysis in alkaline and acidic media - Abba Bala Musa; Mohammad Tabish; Anuj Kumar; Manickam Selvaraj; Muhammad Abubaker Khan; Badria M. Al-Shehri; Muhammad Arif; Muhammad Asim Mushtaq; Shumaila Ibraheem; Yassine Slimani; Saira Ajmal; Tuan Anh Nguyen; et al. (Chemical Engineering Journal, 2023)

Effects of glycosylation on the accumulation and transport of fipronil in earthworm (Eisenia fetida) - Sukun Lin; Li Zhang; Peiwen Zhang; Rilin Huang; Muhammad Musa Khan; Shah Fahad; Dongmei Cheng; Zhixiang Zhang (Environmental Science and Pollution Research, 2023)

RETRACTED ARTICLE: Do anthropogenic and natural factors elevate the haze pollution in the South Asian countries? Evidence from long-term cointegration and VECM causality estimation - Mohammad Musa; Lan Yi; Preethu Rahman; Muhammad Abu Sufyan Ali; Li Yang (Environmental Science and Pollution Research, 2022)

Does location of the households’ matters? Identifying the households’ willingness to pay and preference heterogeneity in advancement of vulnerable ecosystem services: An approach of choice experiment - Muhammad Abu Sufyan Ali; Zhihe Zhang; Sufyan Ullah Khan; Arshad Ahmad Khan; Mohammad Musa; Preethu Rahman; Yousaf Hayat (Environmental Science and Pollution Research, 2022)

Quantifying the spatial preferences heterogeneity to upgrade the endemic ecological attributes for a cleaner environment: Evaluating the feasibility of benefit transfer among sub-basins of an inland river - Muhammad Abu Sufyan Ali; Lan Yi; Sufyan Ullah Khan; Arshad Ahmad Khan; Mohammad Musa; Li Yang (Environmental Science and Pollution Research, 2022)

Cryogenian crustal evolution in western Nigeria shield: whole-rock geochemistry, Sr-Nd and zircon U-Pb-Hf isotopic evidence from Bakoshi-Gadanya granites - Safiyanu Muhammad Elatikpo; Huan Li; Han Zheng; Musa Bala Girei; Jinghua Wu; Abdulgafar Kayode Amuda (International Geology Review, 2022)

Improving the Accuracy of Local Gravimetric Geoid Modelling Using Simulated Terrestrial Gravity Data - Shazad Jamal Jalal; Tajul Ariffin Musa; Ami Hassan Md Din; Wan Anom Wan Aris; Muhammad Faiz Pa’suya (Pure and Applied Geophysics, 2022)

Comparative low lethal effects of three insecticides on demographical traits and enzyme activity of the Spodoptera exigua (Hübner) - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Zhangqian Wang; Hina Gul; Xiaowei Li; Jun Huang; Junaid Ali Siddiqui; Muhammad Qasim; Rui-Long Wang; Muhammad Imran; Mohammed A. Assiri; et al. (Environmental Science and Pollution Research, 2022)

Genesis and timing of Mo mineralization in the Mada Ring Complex, north-central Nigeria: insights from whole-rock geochemistry, Nd-Sr isotopes, zircon U-Pb-Hf isotopes, and molybdenite Re-Os systematics - Musa Bala Girei; Huan Li; Victor Ikechukwu Vincent; Thomas J. Algeo; Safiyanu Muhammad Elatikpo; Saleh Ibrahim Bute; Hafizullah Abba Ahmed; Abdulgafar Kayode Amuda (Mineralium Deposita, 2022)

Performance and welfare of dairy buffaloes subjected to different cooling strategies during subtropical summer - Musa Bah; Muhammad Qamer Shahid; Talat Naseer Pasha; Khalid Javed (Tropical Animal Health and Production, 2022)

Metabolic-based insecticide resistance mechanism and ecofriendly approaches for controlling of beet armyworm Spodoptera exigua: a review - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Xiaowei Li; Zhijun Zhang; Sakhawat Shah; Muhammad Imran; Mohammed A. Assiri; G. Mandela Fernández-Grandon; Nicolas Desneux; Muzammal Rehman; Shah Fahad; et al. (Environmental Science and Pollution Research, 2022)

Lethal and sublethal effects of emamectin benzoate on life-table and physiological parameters of citrus red mite, Panonychus citri - Muhammad Musa Khan; Muhammad Waqar Ali; Muhammad Hafeez; Ze-Yun Fan; Shaukat Ali; Bao-Li Qiu (Experimental and Applied Acarology, 2021)

Petrogenesis of the peralkaline Dutsen Wai and Ropp complexes in the Nigerian younger granites: implications for crucial metal enrichments - Abdulgafar Kayode Amuda; Xiaoyong Yang; Jianghong Deng; Mohamed Faisal; Jinya Cao; Saleh Ibrahim Bute; Musa Bala Girei; Safiyanu Muhammad Elatikpo (International Geology Review, 2021)

Survey of antibodies to Rift Valley fever virus and associated risk factors in one-humped camels (Camelus dromedarius) slaughtered in Maiduguri abattoir, Borno State, Nigeria - Hassan Ismail Musa; Caleb Ayuba Kudi; Muhammad Mamman Gashua; Abubakar Sadiq Muhammad; Abdulyeken Olawale Tijjani; Adamu Saleh Saidu; Sani Mohammed; Saleh Mohammed Jajere; Shuaibu Gidado Adamu (Tropical Animal Health and Production, 2021)

Impact of invasive ant species on native fauna across similar habitats under global environmental changes - Junaid Ali Siddiqui; Bamisope Steve Bamisile; Muhammad Musa Khan; Waqar Islam; Muhammad Hafeez; Imran Bodlah; Yijuan Xu (Environmental Science and Pollution Research, 2021)

Effects of tourism, financial development, and renewable energy on environmental performance in EU-28: does institutional quality matter? - Muhammad Sani Musa; Gylych Jelilov; Paul Terhemba Iorember; Ojonugwa Usman (Environmental Science and Pollution Research, 2021)

Knowledge, attitude, and practices associated with brucellosis among livestock owners and its public health impact in Punjab, Pakistan - Sabir Hussain; Abrar Hussain; Ubaid-ur-Rehman Zia; Syed Musa Raza Naqvi; Muhammad Yasir Zahoor; Muhammad Bilal; Jeffery HO; Olivier A. E. Sparagano (Biologia, 2021)

Emamectin benzoate induced enzymatic and transcriptional alternation in detoxification mechanism of predatory beetle Paederus fuscipes (Coleoptera: Staphylinidae) at the sublethal concentration - Muhammad Musa Khan; Aamir Hamid Khan; Muhammad Waqar Ali; Muhammad Hafeez; Shahbaz Ali; Cailian Du; Zeyun Fan; Muzammil Sattar; Hongxia Hua (Ecotoxicology, 2021)

Influence of cold-storage of eggs of Menochilus sexmaculatus (Coleoptera: Coccinellidae) on the biology and predatory efficiency - QingHeng Tian; YongMei Fan; Muhammad Musa Khan; Jianhui Wu; Liangde Tang (International Journal of Tropical Insect Science, 2021)

In silico predictions on the possible mechanism of action of selected bioactive compounds against breast cancer - Aliyu Muhammad; Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Ibrahim Malami; Ibrahim Babangida Abubakar; Amina Isah kandi; Adam Muntaka Idris; Sabi’u Yusuf; Salihu Muktar Musa; Nagedu Monday; Zak-wan Sidi Umar (In Silico Pharmacology, 2020)

Rabies virus infection in mice up-regulates B7-H1 via epigenetic modifications - Comfort E. Ojedapo; Aliyu Muhammad; Grace S. N. Kia; Musa M. Abarshi; Maryam Abdulazeez; Joy Cecilia Atawodi; Jacob K. P. Kwaga (VirusDisease, 2020)

Effect of hemoglobin polymorphism on performance traits in indigenous chicken genotypes in Nigeria - M. Orunmuyi; H. Muhammad; A. A. Musa; A. K. Olutunmogun; B. I. Nwagu (Tropical Animal Health and Production, 2020)

Ecologically controlling insect and mite pests of tea plants with microbial pesticides: a review - Aisha Lawan Idris; Xiao Fan; Musa Hassan Muhammad; Yachong Guo; Xiong Guan; Tianpei Huang (Archives of Microbiology, 2020)

Induction of Rabies Virus Infection in Mice Brain may Up and Down Regulate Type II Interferon gamma via epigenetic modifications - Maryam Abdulazeez; Grace S. N. Kia; Musa M. Abarshi; Aliyu Muhammad; Comfort E. Ojedapo; Joy Cecilia Atawodi; David Dantong; Jacob K. P. Kwaga (Metabolic Brain Disease, 2020)

Selective and simultaneous detection of cadmium, lead and copper by tapioca-derived carbon dot–modified electrode - Musa Yahaya Pudza; Zurina Zainal Abidin; Suraya Abdul-Rashid; Faizah Md Yasin; Ahmad Shukri Muhammad Noor; Jaafar Abdullah (Environmental Science and Pollution Research, 2020)

Numerical simulation of the impacts of reflected tsunami waves on Pulo Raya Island during the 2004 Indian Ocean tsunami - Teuku Muhammad Rasyif; Syamsidik; Musa Al’ala; Mirza Fahmi (Journal of Coastal Conservation, 2016)

Multi-objective optimization model for water resource management: a case study for Riyadh, Saudi Arabia - Muhammad Al-Zahrani; Ammar Musa; Shakhawat Chowdhury (Environment, Development and Sustainability, 2016)

A novel antimicrobial flavonoid from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad S. Sallau; Aliyu M. Musa; Sani M. Yahaya; James D. Habila; Abdullahi Musa Ismail (Natural Product Research, 2016)

Flavonoids with antimicrobial activity from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad Sani Sallau; Aliyu Muhammad Musa; Dama James Habila; Sani Muhammad Yahaya (Natural Product Research, 2014)